The Impact of Audiovisual Content on Bitcoin’S Transaction Volume and Price; [el Impacto del Contenido Audiovisual en el Volumen de Transacciones y el Precio del Bitcoin] - Campos-Jaque, Z (Universidad Catolica de Colombia, 2025)
This article examines the impact of audiovisual content on Bitcoin’s price and transaction volume, a topic with limited exploration in financial literature. Using correlational and econometric analyses, it investigates audience data from films, series, and documentaries about Bitcoin, alongside public interest metrics from YouTube and Twitch. The results show weak correlations (<0.2) between search levels of most titles and Bitcoin’s financial variables. However, on YouTube, an increase in subscribers to cryptocurrency-related channels has positively and significantly affected Bitcoin’s price and transaction volume. These findings highlight the influence of content creators on cryptocurrency adoption and investment, offering a framework for future research on the impact of audiovisual media on financial markets. © 2025 Universidad Catolica de Colombia. All rights reserved.